2022
DOI: 10.3390/ani12182465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitosan Oligosaccharide on Production Performance, Egg Quality and Ovarian Function in Laying Hens with Fatty Liver Syndrome

Abstract: This study aimed to investigate the role of chitosan oligosaccharide (COS) as an additive in the feed of laying hens with fatty liver syndrome (FLS). Effects on production performance, egg quality as well as ovarian function were determined. A total of 360 Lohmann Pink-shell laying hens (28 weeks old) were randomly assigned to 5 groups (6 replicates × 12 birds). Hens were fed with a basal diet and a high-energy low-protein (HELP) diet supplemented with 0, 200, 400 and 800 mg/kg COS. COS reversed the lowered la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…FLHS is characterized by an excess accumulation of fat in the liver accompanied by liver hemorrhage ( Rozenboim et al, 2016 ). FLHS has been more commonly observed in aged laying hens after having undergone intensive metabolism at peak production ( Shini et al, 2018 ) and could lead to a significant reduction in laying rates and egg quality of laying hens ( Tao et al, 2022 ). A Queensland survey showed that in commercial caged hens, approximately 40% of necropsied hens died because of FLHS ( Shini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…FLHS is characterized by an excess accumulation of fat in the liver accompanied by liver hemorrhage ( Rozenboim et al, 2016 ). FLHS has been more commonly observed in aged laying hens after having undergone intensive metabolism at peak production ( Shini et al, 2018 ) and could lead to a significant reduction in laying rates and egg quality of laying hens ( Tao et al, 2022 ). A Queensland survey showed that in commercial caged hens, approximately 40% of necropsied hens died because of FLHS ( Shini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan oligosaccharide (COS), which is derived from the enzymatic hydrolysis of chitosan, has recently gained attention for its various application such as a health food ( Chantarasataporn et al, 2014 ; Guarnizo et al, 2020 ), plant growth stimulator, feed additive, antimicrobial, and drugs ( Li and Zhu, 2013 ; Chatelain et al, 2014 ; Swiatkiewicz et al, 2015 ; Jia et al, 2019 ; Chang et al, 2020 ; Guarnizo et al, 2020 ; Tao et al, 2022 ; Tzeng et al, 2022 ). In agriculture setting, COS has been found to effectively induce plant innate immunity, improve tolerance to adverse environmental stresses, and promote plant growth.…”
Section: Introductionmentioning
confidence: 99%